Chad Hydraulic projects and peace - Films for the Humanities & Sciences (Firm); Films Media Group (New York, N.Y. : Films Media Group, 2009)
Characterized as an LDC or Least Developed Country, the nation of Chad wrestles with drought, population growth, and resulting tensions between farmers and herders. This program investigates hydraulic projects and mediation initiatives that are fostering relationships between Chad's food growers and its nomadic, livestock-centered cultures. Overviewing the basic causes of Chadian land disputes and competition for water sources as well as failed modernization schemes proposed during the 1960s, the film explores new solutions based on recognizing traditional agriculture and natural migration routes.Viewers witness "sit-down" talks between farmers and herders that could help prevent regional conflicts from flaring up
Chad: Herdsmen vs. Farmers (5:29) -- Chad's Security Situation (2:50) -- Farmers and Herders: Discussion and Debate (4:23) -- Water for Peace Project (3:46) -- Cooperation and Compromise (4:25) -- Wells and Collaboration (3:04) -- Simple Solutions for Peace (1:29)
Encoded with permission for digital streaming by Films Media Group on July 04, 2010
Films on Demand is distributed by Films Media Group for Films for the Humanities & Sciences, Cambridge Educational, Meridian Education, and Shopware
System requirements: FOD playback platform
Keywords: Wealth; Social Ecology; Economic aspects; Effect of human beings on; Social conditions